Influence of varied water gradients on the physiochemical component of rice straw silage - Tan Wei Jun (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 5504 – Research Project. Silage is known to be a better feed for consumption among livestock products. The fermentation process offers several benefits, as it has been proven to enhance nutrients. availability during livestock consumption, less affected by weather damage, especially seen during heavy rain season when most small-scale farmers in Malaysia will start to prepare silage for their livestock. In conjunction, Malaysia has been producing rice straw as a side product of harvesting the rice plant. Most of this by-product is not fully utilized to its maximum and has gone to waste through open burning. The utilization of rice straw silages emerges as a promising technique for enhancing the utility of this by-product in animal feed. Nevertheless, a notable research gap exists in the optimization of water levels to enhance the quality and efficacy of rice straw silages. Hence this research is mainly on determining the possibility of making rice straw silage and determining the effect of water concentration during fermentation preparation on the rice straw silage produced after 21 days of fermentation. The pre-fermentation treatment of rice straw involves five distinct groups and a control, ranging from 50% water concentration to 0 water concentration (control). The impact of water concentration is subsequently evaluated based on chemical parameters (pH and Fleigh value) and physical attributes (color, aroma, texture, presence of mold) in the resulting silage. The findings indicate a statistically significantxi difference at p < 0.05 in both chemical and physical properties as a function of varying water concentrations during the silage preparation. The data derived from the results further imply that water concentrations of 30% and 40% may represent the most optimal levels for rice straw silage preparation. Keywords: Fermentation, Physical Qualities, Rice Straw, Silage, Water Level